Furniture design in district of Temerloh/ Nor Azura Mohammed Shariff - Mohammed Shariff, Nor Azura (2011)
The intention of this paper is to describe the finding of research on furniture design in district of Temerloh by owner companies and customers. It aims to anticipate what the future holds and how designers may respond accordingly. The paper focuses on a research project which examined the responses of respondent / customer users to various aspects of furniture design. Several of questions were taken from two companies randomly selected subject and 100 copies of questionnaires are distributed among the respondents / customers. Data obtained from I1ham Design Furniture Company and Courts Mammoth Company.